Dormancy break induced by gibberellic acid and in vitro germination of seeds and zygotic embryos of Prunus campanulata Maxim - Isabel Homczinski; Jonathan Matheus dos Santos; Daniela Sanson; Alexandre Techy de Almeida Garrett; Fabiana Schmidt Bandeira Peres (Evidência, 2023)
Prunus campanulata is a species largely adopted for landscape composition in Brazil with limited seedling production by seed dormancy, lacking studies about in vitro propagation. This study aims to evaluate different P. campanulata seed pretreatments on germination, and the effect of GA3 on dormancy break and seedlings biometry. Seeds were processed in three treatments: complete seeds, seeds without endocarp, and isolated zygotic embryos incubated in a WPM medium containing different GA3 concentrations (0.0, 2.0, and 4.0 mg L-1). After 30 days of in vitro incubation were evaluated the germination percentage, mean germination time, percentage of normal seedlings, percentage of seedlings with leaves, and survival percentage were. Seedlings greater than 3.0 cm were selected for ex vitro adaptation, evaluating after 32 days the biometric variables: total length, aerial part length, root length, and the number of leaves. Complete seeds do not germinate, suggesting dormancy associated with the endocarp, whereas seeds without endocarp and isolated zygotic embryos showed the same germination rate, with no effect on GA3. The GA3 promoted greater seedling growth at concentrations between 1.89 mg L-1 for the total length of the isolated zygotic embryo and 2.24 mg L-1 for the length of the aerial part of seeds without endocarp. In conclusion, seed processing, i.e., removing the endocarp or isolating the zygotic embryo can overcome dormancy, improving germination and seedling production of P. campanulata in vitro.